Thrombocytopenia as a surrogate marker of hepatosplenic schistosomiasis in endemic areas for Schistosomiasis mansoni - Sandra Costa Drummond; Pedro Nunes Pereira; Alba Otoni; Bruna Assis Chaves; Carlos Maurício Antunes; José Roberto Lambertucci (Revista da Sociedade Brasileira de Medicina Tropical, 2014)
Introduction This study aimed to evaluate whether a low platelet count is a good surrogate marker of hepatosplenic schistosomiasis (HSS) in a rural area of Brazil. A small district in southeastern Brazil, with a population of 1,543 individuals and a 23% prevalence of schistosomiasis, was selected for this investigation. Methods In July 2012, 384 volunteers were subjected to clinical, ultrasonography (US), and laboratory examinations, including stool sample analysis. The HSS patients were classified into four groups: Group 1 consisted of patients with a spleen >13cm and liver fibrosis; Group 2 consisted of patients with a palpable spleen and spleen>13cm measured by US; Group 3 consisted of patients with a spleen >13cm measured by US; and Group 4 consisted of patients with a palpable spleen. Results Eight patients were in Group 1 (2.1%), twenty-one were in Group 2 (5.5%), eight were in Group 3 (2.1%), and eighteen were in Group 4 (4.7%). A significant difference in the mean platelet counts was observed between the patients with and without HSS (p<0.01). Based on the receiver operating characteristic (ROC) curve (platelet count <143,000/mm3), the sensitivity was greater than 92% in all groups, and the specificity varied from 44.4% to 75%. Conclusions We concluded that in endemic areas, thrombocytopenia demonstrates good sensitivity for detecting HSS and may be used as a screening tool to identify patients with HSS.